Localized giant solitary fibrous tumor of the scrotum: a rare case report and literature review - Jiang, Shuangjian (J Int Med Res, 2019)
BACKGROUND: A solitary fibrous tumor (SFT) is a fibroblastic mesenchymal tumor initially thought to originate from the pleura but that may arise at almost any anatomic site. It is mostly benign, and surgical resection is usually the best treatment option. An SFT involving the scrotum is extremely rare. Case presentation: We herein report an uncommon case of a 22-year-old man who presented with a huge asymptomatic scrotal mass that had begun growing 3 years before presentation. Contrast-enhanced computed tomography revealed a heterogeneous, well-circumscribed scrotal mass with soft tissue density. No invasion of the surrounding organs, distal metastasis, or lymph node swelling was present. Complete resection of the mass was successfully performed. The specimen was a 14.5 × 12.0 × 9.5 cm encapsulated tumor that weighed 970 g. After pathological analysis, we confirmed the diagnosis of SFT. This diagnosis was based on clinical findings, histological morphology, and immunohistochemistry. No recurrence or metastasis was observed during a 3-year follow-up. CONCLUSION: SFTs have an unpredictable clinical course, and they are difficult to diagnose and easy to misdiagnose. A scrotal location is extremely rare. Complete resection of the mass is the treatment of choice and is associated with a high success rate and low recurrence rate.